2021
DOI: 10.3389/fnins.2021.664363
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Distinct Topologically Structural Connectivity Patterns in Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder

Abstract: BackgroundPrevious neuroimaging studies have described shared and distinct neurobiological mechanisms between autism spectrum disorders (ASDs) and attention-deficit/hyperactivity disorder (ADHD). However, little is known about the similarities and differences in topologically structural connectivity patterns between the two disorders.MethodsDiffusion tensor imaging (DTI) and deterministic tractography were used to construct the brain white matter (WM) structural networks of children and adolescents (age range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 78 publications
0
36
1
Order By: Relevance
“…There was also one DTI study that compared DCD with ADHD (Langevin et al, 2014). Section 3.3.2 of the results illustrate studies that compared ASD and ADHD (Table 5), 10 of which conducted structural MRI (Albajara et al, 2020;Baribeau et al, 2019;Bethlehem et al, 2017;Boedhoe et al, 2020;Brieber et al, 2007;Fine et al, 2014;Lim et al, 2015;Mostofsky et al, 2007;Park et al, 2018;Vasa et al, 2012), three DTI (Ameis et al, 2016;Aoki et al, 2017;Qian et al, 2021), two resting-state fMRI (Di Martino et al, 2013;Jung et al, 2019), and three multimodality MRI (Cordova et al, 2020;Henry et al, 2019;Ray et al, 2014).…”
Section: Results Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also one DTI study that compared DCD with ADHD (Langevin et al, 2014). Section 3.3.2 of the results illustrate studies that compared ASD and ADHD (Table 5), 10 of which conducted structural MRI (Albajara et al, 2020;Baribeau et al, 2019;Bethlehem et al, 2017;Boedhoe et al, 2020;Brieber et al, 2007;Fine et al, 2014;Lim et al, 2015;Mostofsky et al, 2007;Park et al, 2018;Vasa et al, 2012), three DTI (Ameis et al, 2016;Aoki et al, 2017;Qian et al, 2021), two resting-state fMRI (Di Martino et al, 2013;Jung et al, 2019), and three multimodality MRI (Cordova et al, 2020;Henry et al, 2019;Ray et al, 2014).…”
Section: Results Of Studiesmentioning
confidence: 99%
“…The sample size of these studies varied from n = 10 to n = 723. Fifteen studies used structural MRI to measure brain size (Albajara et al, 2020; Baribeau et al, 2019; Bethlehem et al, 2017; Boedhoe et al, 2020; Brieber et al, 2007; Caeyenberghs et al, 2016; Fine et al, 2014; Langevin et al, 2015; Lim et al, 2015; Mahajan et al, 2016; Mostofsky et al, 2007; Nickel et al, 2018; Shaw et al, 2016; Shook, 2015; Vasa et al, 2012), five studies used diffusion tensor imaging for structural connectivity (Ameis et al, 2016; Aoki et al, 2017; Langevin et al, 2014; Qian et al, 2021; Shook, 2015), and eight studies used resting‐state fMRI to investigate functional connectivity between brain regions (Dajani et al, 2019; Di Martino et al, 2013; Jung et al, 2019; McLeod et al, 2014, 2016; Rohr et al, 2021; Shook, 2015; Wan et al, 2019). There were also three multimodality studies—structural and resting‐state MRI (Cordova et al, 2020; Henry et al, 2019; Ray et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Variation in global white matter organisation has been linked to differences in general cognitive abilities, reading and mathematics skills (Bathelt et al, 2018a;Bathelt et al, 2019, Koenis et al, 2015. It has also been implicated in neurodevelopmental disorders such as ADHD and ASD (Beare et al, 2017;Cao et al, 2013;Qian et al, 2021), with both shared and distinct differences reported in white matter organisation across children with different neurodevelopmental disorders (Ameis et al, 2016;Qian et al, 2021).…”
Section: Linking Transdiagnostic Profiles To Aetiological Factorsmentioning
confidence: 99%
“…Variation in global white matter organisation has been linked to differences in general cognitive abilities, reading and mathematics skills (Bathelt et al, 2018a; Bathelt et al, 2019, Koenis et al, 2015). It has also been implicated in neurodevelopmental disorders such as ADHD and ASD (Beare et al, 2017; Cao et al, 2013; Qian et al, 2021), with both shared and distinct differences reported in white matter organisation across children with different neurodevelopmental disorders (Ameis et al, 2016; Qian et al, 2021). Examples of structural neural substrate variation implicated in multiple neurodevelopmental conditions include the corticostriatal circuits, thalamic radiations, and interhemispheric pathways (Ameis et al, 2016; Aoki et al, 2017; Arnsten & Rubia, 2012; Tung et al, 2021; Zhao et al, 2022).…”
Section: Transdiagnostic Approaches To Neurodevelopmentmentioning
confidence: 99%
“…More than half of children on the autism spectrum have symptoms of attention de cit disorder [11] . Through neuroimaging studies mapping the social brain showed patterns of associations were similar in ASD and ADHD, also supporting a common underlying biology and boundaries between these disorders [12,13] .…”
Section: Introductionmentioning
confidence: 96%